Assessment of energy and exergy efficiencies of a grate clinker cooling system through the optimization of its operational parameters - Ahamed, Jamal Uddin; Madlool, N.A.; Saidur, Rahman; Shahinuddin, M.I.; Kamyar, A.; Masjuki, Haji Hassan (Elsevier, 2012)
Grate coolers are widely used in cement industries to recover heat from hot clinker, coming out from the rotary kiln. This study focuses on improving the energy, exergy and recovery efficiencies of a grate cooling system through the optimization of its operational parameters such as masses of cooling air and clinker, cooling air temperature, and grate speed. It has been found that the energy and recovery energy efficiencies of a cooling system can be increased by 1.1 and 1.9, respectively, with every 5 mass increases of cooling air. Similarly, it has been estimated that energy and recovery energy efficiencies can be increased by 2.0 and 0.4 with every 5 increase of cooling temperature. The exergy and its recovery efficiencies found to be increased by 3.6 and 2.2, respectively, for the same condition. Energy efficiency and energy recovery efficiencies are increased by 3.5 and 1.4 with every 9.1 increase of grate speed. Using heat recovery from the exhaust air, energy and exergy recovery efficiencies of the cooling system found to be increased by 21.5 and 9.4, respectively. It has been found that about 38.10 and 30.86 energy cost can be saved by changing mass flow rate of clinker and mass flow rate of cooling air, respectively.